2009
DOI: 10.1021/es9014212
|View full text |Cite
|
Sign up to set email alerts
|

Effect-Directed Identification of Naphthenic Acids As Important in Vitro Xeno-Estrogens and Anti-Androgens in North Sea Offshore Produced Water Discharges

Abstract: Produced water from offshore oil production platforms represents the largest direct discharge of effluent into the offshore environment. Produced water effluents contain a complex mixture of substances which are known to bind to the estrogen receptor (ER) and antagonize the androgen receptor (AR). Short-chain petrogenic alkylphenols have been identified as responsible for around 35% of the ER agonist activity measured in vitro while the compounds responsible for antagonizing the androgen receptor are unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
126
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(135 citation statements)
references
References 37 publications
4
126
2
Order By: Relevance
“…The effect of commercial naphthenic acids and of wastewater extracts from North Sea oil production on the yeast androgen bioassay was recently examined by Thomas et al [28], and the material was found to be antiandrogenic. This finding raises the possibility that oil sands naphthenic acids may be antiandrogenic to fish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of commercial naphthenic acids and of wastewater extracts from North Sea oil production on the yeast androgen bioassay was recently examined by Thomas et al [28], and the material was found to be antiandrogenic. This finding raises the possibility that oil sands naphthenic acids may be antiandrogenic to fish.…”
Section: Discussionmentioning
confidence: 99%
“…Male fathead minnows exposed to 5 mg/L of the same extract had lower plasma levels of 11-ketotestosterone, whereas those exposed to 10 mg/L had lower concentrations of both testosterone and 11-ketotestosterone. Thomas et al [28] also raised the possibility that PAHs can bind to androgen receptors. It is known that tailings porewater contained PAHs [2], and they were present in sediment and insects from the Demonstration and Bison Pond [3].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dawson et al (1996) demonstrated the toxicity of aromatic acids, including benzoic acid and a range of phenylalkanoics, using Xenopus embryos, whereas Zhao et al (1998) reported the toxicity of a range of benzoic acids to Vibrio fischeri, Daphnia magna and carp. More recently, Thomas et al (2009) showed a mixture of 2 0 -, 3 0 -and 4 0 -isobutylphenyl-4-pentanoic acids as environmental androgen receptor antagonists. Despite this, there is insufficient information on the metabolism of aromatic alkanoic acids, and the microorganisms involved in their biodegradation are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Their main characteristic is higher polarity which, as a consequence, affords higher water solubility and bioavailability/toxicity. [62][63][64] Furthermore, this fraction can also contain transformation products generated through weathering, such as oxidated polycyclic compounds which can be present at even higher concentrations than the parent compounds. 65 These have been reported in marine environmental matrices at toxic levels 66,67 and can be persistent.…”
Section: -61mentioning
confidence: 99%